The role of personalized services and control: An empirical evaluation of privacy calculus and technology acceptance model in the mobile context. Issue 3 (2nd July 2016) - Liu, Zhan; Shan, Jialu; Pigneur, Yves
ABSTRACT: The past few years have witnessed an explosive growth in the use of smartphones. Such widespread use brings with it concerns over the protection of privacy. Building upon existing privacy concern literature, this study has developed a theoretical framework that combines a privacy calculus model with a technology acceptance model (TAM) in the mobile application context. Also examined is the role of personalized services and users' perceived information control in this domain. Based on a study of 308 participants, the results reveal that perceived enjoyment has replaced perceived ease-of-use as a main predictor of perceived behavioral intentions in a mobile TAM. The findings also show that personalized services and users' perceived information control have a strong effect on both privacy calculus and mobile TAM.